Highway Addressable Remote Controller Using ATMega328 - Dr.P.Thirusakthimurugan, R.Suvedha (International Journal of Advanced Science and Technology, 2020)
This paper deals with intelligent system design of an Industrial controller with AVR RISC Microcontroller ATMega328, based on Highway Addressable Remote Transducer (HART) protocol. The controller’s application could be customized for any specific needs. The paper dwells on the systems architecture, system hardware design and customized design relevant to controller’s functionality. The paper illustrates the customization of the generic controller for a specific task. The proposed system monitors the process temperature and then registers it on the LED display and the process signal 4-20mA is transmitted to the controller through a cable. The controller, furthermore, takes decision based on the algorithm developed in the microcontroller, sends control signal in the form of FSK through the same cable to the actuator. The paper demonstrates how the customized functionality is achieved in software and hardware. This intelligent controller reduces one-way cable cost, increases reliability and accuracy, immunity to noise, operational flexibility and has better stability.